Glucose‐6‐phosphate dehydrogenase deficiency in Italian blood donors: prevalence and molecular defect characterization. (18th October 2013) - Maffi, D.; Pasquino, M. T.; Mandarino, L.; Tortora, P.; Girelli, G.; Meo, D.; Grazzini, G.; Caprari, P.
<x xml:space="preserve">Abstract</x> Background In the countries with high G6PD deficiency prevalence, blood donors are not routinely screened for this genetic defect. G6PD deficiency is often asymptomatic, blood donors may be carriers of the deficiency without being aware of it. The aim of the study was to evaluate the prevalence of G6PD deficiency among the Italian blood donors. Design and Methods From October 2009 to April 2011, 3004 blood donors from a large hospital transfusion centre were screened for G6PD deficiency using differential pH‐metry and the characterization of G6PD mutations was performed on G6PD‐deficient subjects. The haematological features of G6PD‐deficient and normal donors were also compared. Results Thirty‐three subjects (25 men and 8 women) with low G6PD activity were identified, corresponding to 1·1% of the examined blood donor population. The frequencies of class II severe alleles (Mediterranean, Valladolid, Chatham and Cassano) and class III mild alleles (Seattle, A‐ and Neapolis) were 48% and 43%, respectively. The haematological parameters of G6PD‐ donors were within normal range; however, the comparison between normal and G6PD‐ class II donors showed significant differences. Conclusion In Italy, the presence of blood donors with G6PD deficiency is not a rare event and the class II severe variants are frequent. The identification of G6PD‐deficient donors and the characterization of the molecular variants would prevent the use of G6PD‐deficient RBC units when the haemolytic complications could be relevant especially for high risk patients as premature infants and neonates and patients with sickle cell disease submitted to multiple transfusions.